(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate whether the type and the remaining amount of endodontic sealer interfere with the adhesion of resin-based cement to dentin. For this, 25 crowns of bovine teeth were used with three specimens in each crown. The specimens were divided into 4 experimental groups (n = 15): Group EF (+) - Endofill sealer with surface partially covered with endodontic sealer (n = 15), Group AHP (+) - AH Plus sealer with surface partially covered with endodontic sealer (n = 15), Group EF (-) - Endofill sealer with endodontic sealer removed in a semiautomatic polisher with a # 800 sanding disc for 30 seconds, Group AHP (-) - AH Plus sealer with endodontic sealer removed in one semiautomatic polisher with sanding disc of size # 800 for 30 seconds, and a control group (n = 15): Group C - without endodontic sealer. Silicone matrices of surgical catheters were placed on the dentin surface and filled with resin-based cement. After the polymerization of the cement, the specimens were subjected to mechanical tests of shear strength in a universal testing machine. The necessary force for the displacement of the specimen was recorded. The data obtained were analyzed by ANOVA and Tukey statistical tests with a significance level of 5%. The results showed that there were statistical differences between the control group and the experimental groups, and there was no statistically significant difference between the experimental groups. It can be concluded that the presence of endodontic sealer interferes with the adhesion of resin-based cement to dentin, regardless of the type of endodontic sealer used and the remaining amount.